Predicting bone scan positivity in non-metastatic castration-resistant prostate cancer - Moreira, Daniel M. (Prostate Cancer Prostatic Dis, 2015)
OBJECTIVES: To evaluate PSA levels and kinetic cutoffs to predict positive bone scans for men with non-metastatic castrate resistant prostate cancer (CRPC) from the Shared Equal Access Regional Cancer Hospital (SEARCH) cohort. METHODS: Retrospective analysis of 531 bone scans of 312 clinically CRPC patients with no known metastases at baseline treated with a variety of primary treatment types in the SEARCH database. The association of patients’ demographics, pathological features, PSA levels and kinetics with risk of a positive scan was tested using generalized estimating equations. RESULTS: A total of 149 (28%) scans were positive. Positive scans were associated with younger age (OR=0.98; P=0.014), higher Gleason scores (relative to Gleason 2-6, Gleason 3+4: OR=2.03, P=0.035; Gleason 4+3 and 8-10: OR=1.76, P=0.059), higher pre-scan PSA (OR=2.11; P<0.001), shorter pre-scan PSA doubling time (PSADT; OR=0.53; P<0.001), higher PSA velocity (OR=1.74; P<0.001) and more remote scan year (OR=0.92; P=0.004). Scan positivity was 6%, 14%, 29% and 57% for men with PSA <5, 5-14.9, 15-49.9 and ≥50ng/mL, respectively (P-trend <0.001). Men with PSADT ≥15, 9-14.9, 3-8.9 and <3 months had a scan positivity of 11%, 22%, 34% and 47%, correspondingly (P-trend <0.001). Tables were constructed using PSA and PSADT to predict the likelihood of a positive bone scan. CONCLUSIONS: PSA levels and kinetics were associated with positive bone scans. We developed tables to predict the risk of positive bone scans by PSA and PSADT. Combining PSA levels and kinetics may help select patients with CRPC for bone scans.